20 years outcomes after hybrid coronary revascularization. (3rd October 2022) - Gadelkarim, I; Verevkin, A; Von Aspern, K; Deshmukh, N; Holzhey, D; Saeed, D; Davierwala, P; Misfeld, M; Borger, M A
Abstract: Background: Hybrid coronary revascularization (HCR) is a Heart Team directed strategy for selected patients with mutlivessel coronary artery disease. However, data on long-term results are lacking. Purpose: To analyse long-term outcomes after HCR over a 20-year period. Methods: Between 1996 and 2020, a total of 2667 consecutive patients underwent minimally invasive direct coronary artery bypass grafting (MIDCAB) at our institution, and 177 of these were planned HCR cases. Planned HCR consisted of a MIDCAB procedure to the left anterior descending (LAD) artery preceded or followed by percutaneous intervention (PCI) of non-LAD lesions. We excluded patients who underwent prior cardiac surgery and patients with emergency indications for revascularization (either surgical or transcatheter). Short- and long-term results for the entire cohort were analysed and a propensity score-matched comparison was performed between MIDCAB-first and PCI-first revascularization strategies. Results: The mean age of all patients was 67 (±12) years with 37% suffering from diabetes (n=67). The median time-interval between MIDCAB and PCI was 22 days (IQR 5–53). Thirty-day mortality was 3.9% for the entire cohort. A total of 9 patients (5.0%) underwent early target vessel revascularization; 4 patients (2.2%) involving the LAD following the MIDCAB procedure and 5 patients (2.8%) involving non-LAD vessels following PCI. The rate of incomplete revascularization following completion of HCR was 25.4% (n=45). Long-term survival was 53.5% at 15 years and 30.4% at 20 years and the rate of repeat revascularization with PCI or surgery was 15.8% (n=28). The propensity matched sub-analysis of MIDCAB- versus PCI-first strategy showed no significant differences with regard to short- and long-term outcomes. Age (HR: 1.01, 95% CI 0.98–1.04, p=0.042) and incomplete revascularization (HR: 2.60, 95% CI 1.26–5.34; p=0.01) were independent risk factors for follow-up mortality. Conclusions: Hybrid coronary revascularization as a less invasive strategy for selected patients is associated with acceptable 20-year survival. However, repeat revascularization rates are substantial. Funding Acknowledgement: Type of funding sources: None.